Niemieccy myśliciele w Polsce : O działalności naukowej i translatorskiej Elżbiety Paczkowskiej-Łagowskiej wspomnienie pośmiertne - Citkowska-Kimla, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
In this analysis my aim is to highlight the achievements of Elżbieta Paczkowska-Łagowska in the study of German ideas. A secondary aim of the consideration is to demonstrate that it is to Elżbieta Paczkowska-Łagowska that we in Poland owe the knowledge of some German names which, although important for the doctrinal map of the world, would not be known in Poland if it were not for her work. Out of the enormous number of publications by the industrious researcher and translator of the works German thinkers, two figures have been selected to show the broad spectrum of Elżbieta Paczkowska-Łagowska’s scientific research and to highlight her exceptional contribution to the introduction of German philosophers, thinkers or essayists into the scope of interest of Polish science. These include Helmuth Plessner, the founder of political anthropology, and Golo Mann, a historian and political scientist. Both thinkers would not be known in Poland if it were not for the translating and scientific efforts of Paczkowska-Łagowska. The choice of these two German scholars was dictated by the symbolic illustration of the main research of the author of The Logos of Life, the essence of which is the study of man and history.
Keywords: Paczkowska-Łagowska, Elżbieta (1948–2021); Plessner, Helmuth (1892–1985); Golo Mann; antropologia polityczna; natura ludzka; polityka; historia; historiografia; totalitaryzm